(2-3x)+(3-4x)=

Simple and best practice solution for (2-3x)+(3-4x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2-3x)+(3-4x)= equation:


Simplifying
(2 + -3x) + (3 + -4x) = 0

Remove parenthesis around (2 + -3x)
2 + -3x + (3 + -4x) = 0

Remove parenthesis around (3 + -4x)
2 + -3x + 3 + -4x = 0

Reorder the terms:
2 + 3 + -3x + -4x = 0

Combine like terms: 2 + 3 = 5
5 + -3x + -4x = 0

Combine like terms: -3x + -4x = -7x
5 + -7x = 0

Solving
5 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -7x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -7x = 0 + -5
-7x = 0 + -5

Combine like terms: 0 + -5 = -5
-7x = -5

Divide each side by '-7'.
x = 0.7142857143

Simplifying
x = 0.7142857143

See similar equations:

| B-5+2b=26 | | 110-x+4x=180 | | 4x^6+24x^5+36x^4=4x^2+16x+16 | | 0.7x-0.7(6-x)=4.9 | | b^2-5/3b=0 | | 8-3z=(-2+6)+6(3z+4) | | 4x+16z=y | | a+b+b+b+80+99=100 | | 8(14)-3(2[14]+5)= | | -13-9x=-41 | | 7x-3(8-x)=3 | | x^2-8x+16-64= | | x^2+24x+26=16x+16 | | 8(14)-3(2[14]+5)=13 | | 25+7a=a+12 | | 7x-8y+40=0 | | 3(-2+x)=15 | | (4x-36)+(3x+20)=180 | | -30-7=10x+21 | | B-6+4b=15 | | 4/1*4/8 | | 11y+-3=13y-3 | | 3.100-2.076= | | 33-6n=5(1-4n) | | 6.8p-8=8p-8 | | x+2*x+3*x+4*x=40 | | 3.4-0.972= | | -4n-6(5+4n)=-10-8n | | -20+x=x+18 | | y=40+6x | | graphiney=18-1.25x | | 6x^2+17x=28 |

Equations solver categories